The ascidian Lissoclinum patella, the patellamides and copper - Baur, Philipp; Comba, Peter; Gahan, Lawrence; Scholz, Christian (Australian journal of chemistry, 2023)
The ascidian species Lissoclinum patella is found, amongst other places, around Heron Island on the Great Barrier Reef, Australia. L. patella has a cyanobacterial symbiont, Prochloron didemni, known to produce various cyclic peptides, including quantities of the cyclic pseudo-octapeptides, the patellamides. Patellamides are of pharmaceutical interest and have attracted the curiosity of coordination chemists because they can form quite stable mono- and di-nuclear transition metal complexes, particularly with copper(ii). For some patellamide derivatives, the binding of two CuII centres is cooperative and solution equilibria involving metal-free peptides, mono- and di-nuclear copper(ii) complexes, and various functions of these complexes have been described. These studies were also driven by the observation that the ascidians possess copper concentrations in excess of that in the seawater around Heron Island, and accumulation factors of approximately 104 have repeatedly been reported. New data presented here, based on inductively coupled plasma atomic emission spectroscopy (ICP-OES) and ICP-mass spectromety (MS) measurements, indicate that the 104 factor is overestimated and a factor >500 and up to approximately 3000 is more realistic.
Published: 9 December 2022
Gesehen am 10.05.2023